Translation and psychometric testing of Indonesian Version of Chronic Kidney Disease– Symptom Burden Index - Wasilah, Hinin; Natashia, Dhea; Huang, Chen-Hui; Chen, Hsing Mei; Yen, Miaofen (Universitas Airlangga, 2023)
Introduction: Chronic Kidney Disease Symptom Burden Index (CKD-SBI) is an instrument measuring symptom burden developed by Almutary and colleagues in 2015 to refine the identification of symptom burden in chronic kidney disease population. This instrument has not been tested for Indonesian language, thus, the aim of study was to translate and psychometrically testing the Indonesian version of CKD-SBI. Methods: This study design was cross-sectional study. The study methods were divided into translation and psychometric testing. The translation was conducted by adapting Guillemin and Beaton's guidelines. The psychometric properties determined 320 hemodialysis patients with several inclusion criteria such as above 18 years old, regularly receiving hemodialysis for more than 3 months. Patients with cognitive impairment, psychiatric patients, and in critical condition were excluded. Results: The item content validity index of the Indonesian version was 0.92, and the subscale content validity was 0.78. The instrument demonstrated convergent validity with the Kidney Disease Quality of Life. Excellent internal consistency was demonstrated based on a Cronbach's alpha coefficient of .91 and a subscale ranging from 0.86 to 0.92. The confirmatory factor analysis showed that the five factors of English Version did not fit the Indonesian version. Conclusions: Translated Indonesian versions of CKD-SBI can be used as instruments to assess symptom burden among patients with hemodialysis. By assessing symptom burden, we hope nurses in the hospital are able to decide effective symptom management to increase the health-related quality of life among these populations.